Bringing the Pandemic Home: The Shifting Realities of Intimate Violence for Disabled People in the Time of COVID-19 - Shelton, Sam Z. (Disability Studies Quarterly, 2021)
In this article, I explore the shifting realities of intimate violence for disabled people in the midst of a global pandemic. I argue that the social and political vulnerabilities of these pandemic times, which have (often deliberately) been compounded by conservative political regimes (like the Trump administration in the United States), make it urgent for anti-violence advocates/activists to root our organizing in the intersectional crip framework of disability justice. I suggest several avenues for intervention and resistance that are grounded in radical visions of care and access advanced by such disability justice theorists as Mia Mingus (2017), Leah Lakshmi Piepzna-Samarasinha (2018), and Sins Invalid (2016). In particular, I describe how engaging with these visions and concepts opens up alternative pathways for a more inclusive, liberatory, and transformative anti-violence praxis. My purpose in writing this article is to promote further conversation about the impacts of COVID-19 on intimate violence and to support critical action centered around the lived experiences and access needs of disabled/crip peoples, especially those who have been most directly impacted by the pandemic (e.g., poor and homeless disabled people, queer and trans disabled people, and disabled people of color).